Fluorescence-based detection of nitroaromatics using a luminescent second sphere adduct self-assembled by charge-assisted hydrogen bonds. Issue 3 (19th December 2017) - Duan, Wen-Long; Wang, Hao-Cheng; Martí-Rujas, Javier; Guo, Fang
Abstract : Photo-luminescent metal organic materials self-assembled via second sphere coordination using luminescent ligands show good selectivity to detect trace amounts of nitroaromatics. Abstract : Using second sphere interactions (outer sphere) by means of charge-assisted hydrogen bonds, a new Cd luminescent metal organic material has been prepared and successfully applied to the detection of trace amounts of nitrobenzene, 2-nitrotoluene and 3-nitrotoluene. The luminescence properties of the Cd crystal display selectivity and sensitivity to nitrobenzene derivatives with a high quenching efficiency.